Montessori Method of Teaching: The Key to Learning and Teaching of Mensuration of Solid Shapes, a Case of a Private School in Zimbabwe - , Sunzuma Gladys, Zezekwa Nicholas (Archives of Current Research International, 2016)
The study sought to find out how efficient the Montessori Method of Teaching, MMT is on Ordinary level (‘O’ level) pupils’ achievement in mensuration. This research was carried out in Zimbabwe, at a private school over a period of four months, using a sample of 32 ‘O’ level pupils. The researchers constructed two Mensuration Achievement Tests (MAT) that were used as data collection instruments. Descriptive statistics such as mean and standard deviation were employed in this study. Findings from this study showed that pupils taught with MMT were advanced in achievement than those taught using Conventional lecture Method, CLM. This was indicated by the major variation between the mean scores of pupils taught mensuration with MMT and those taught with the Conventional in the two tests. From the findings it is recommended that mathematics teachers should be trained on the use of Montessori Method in the teaching and learning of mensuration with a vision to making learning of the concepts important, applicable and motivating.